Cybergenic Presidential Candidates of Third Parties in the United States: The Analysis of Selected Political Campaigns with the Key Role of New Media - Popielec, Dominika (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
This article focuses on selected political campaigns of the Third Parties in the United States. The main purpose of this work is to present how these candidates promote themselves and communicate with voters. Traditional and new media are playing a crucial role in public life during presidential elections. Not only do they inform society but also are a tool of political communication. Voters can get to know a candidate and his/her election program via the media. Journalists are conducting interviews with main candidates, especially the Democrats and Republicans, which are leaders in the polls. But what should the candidates from other parties do? Those who do not appear very often in the mainstream media? How do they gain public support for their ideas? Do we insist on a telegenic president, as William F. Buckley indicated, or a cybergenic president in the contemporary world? Considering the increasing role of the Internet in modern society, these candidates use new new media to promote themselves. Therefore, in this article I will describe the importance of new media, their effectiveness in presidential campaigns and a cybergenic candidate as a standard of modern political communication